Luteinizing Hormone Release in Kisspeptin treated Pre- pubertal Murrah Buffaloes - Pandey, Himanshu; Nishant Kumar; Kumar, Dheeraj (The Indian Journal of Animal Reproduction, 2024)
Kisspeptin is a neuropeptide that governs the reproductive axis upstream to GnRH. Present study was undertaken to compare the effect of different doses of kisspeptin on release of luteinizing hormone (LH) in Murrah buffaloes during pre-pubertal period. Twenty four pre-pubertal buffalo heifers were selected and divided into 4 groups (Control, T1, T2 and T3), having 6 animals in each group. Kisspeptin-10 was administered at the dose of 2 μg/kg body weight, 1.5 μg/ kg body weight, 1μg/kg body weight respectively in T1, T2 and T3 group along with administration of equal volume of NSS in control group. Blood sampling was done at every 20 minutes interval beginning with zero minutes up to 2 hours and analyzed for LH concentration. Results indicated that LH concentration was significantly (p<0.05) higher in T1 group. The peak level of LH was recorded at 20 minutes post administration and falls to basal level at 60 minutes post administration. Although increased LH concentration was observed in other treatment groups but it was lower than T1 group. No LH peak or rise in LH level was observed in control group. The result of this study indicates that during the pre-pubertal period, administration of Kisspeptin causes dose dependent increase in LH concentration and peak level was seen at 2 μg/kg body weight of dose.